Rapid and sensitive rGO/AuNP-based electrochemical nano-biosensor for detection of E. coli and S. aureus in less than an hour - Sirdeshmukh, Vedashree V.; Joglekar, Shreeram S.; Joshi, Preeti Nigam; Kale, Anup A. (AIP Advances, 2025)
Improved diagnostic screening has become critical for bacterial infection identification and prevention. The sensitivity, reliability, repeatability, detection time, and specificity of a test or tool are critical for its translation to application. Electrochemical detection methods are quick and can provide point-of-care diagnosis. We report on reduced graphene oxide/gold (rGO-AuNP) nanocomposites that enabled highly sensitive and quick detection of harmful bacteria, such as E. coli and S. aureus. The technique involved employing rGO as a nano-carrier and Au as a bioactive surface to bind particular antibodies for electrochemical immunoassays. The current approach is culture-independent and does not require sample processing for bacterial detection. It is a pathogen detection technology that uses rGO-AuNP as an electrochemical transducer platform and target particular antibodies for E. coli and S. aureus to obtain improved sensitivity and speed. Differential pulse voltammetry was used to detect infections. These findings demonstrated that rGO-AuNp nanocomposites have up to three times the sensitivity of rGO and AuNP alone. Importantly, the antibody linked bioactive screen-printed electrodes remained stable for more than a month, allowing just electrochemical measurements to be performed at the time of detection. This allowed for pathogen detection in less than an hour. The limit of detection for both E. coli and S. aureus was 2 CFU/ml, making it extremely sensitive. An electrochemical sensor was showing a linear response with R2 0.98. According to the physicochemical evaluation of nanocomposites, the improved sensitivity and stability were caused by a lowered bandgap in composites and uniform distribution of AuNPs on a rGO nano-template. (c) 2025 Author(s). All article content, except where otherwise noted, is licensed under a Creative Commons Attribution-NonCommercial-NoDerivs 4.0 International (CC BY-NC-ND) license (https://creativecommons.org/licenses/by-nc-nd/4.0/).